DOMINASI KAPITALISME DALAM SISTEM PERS INDONESIA PASCA REFORMASI - Hendra Alfani (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
The dynamics of the Indonesian press continue to evolve as the times progress, where in that development, the situation and political changes of power and economic forces have caused the press to transform into industrial forces that are part of global capitalism.The press, which should be called a mirror depicting the state of society, begins to experience a shift, even trapped in the trap of global capitalism octopus. Therefore, seeing the dynamics of the Indonesian press should be placed in the wider social totality, as an integral part of the economic, social, and political processes that take place and develops in society. Press institutions, media industry structures, and interactions between the press and the various groups that produce and consume media content text, are part of a dynamic process of political, economic, and social dynamics of the community to be carefully scrutinized.